Anti-NGF treatment worsens subchondral bone and cartilage measures while improving symptoms in floor-housed rabbits with osteoarthritis - Menges, Stephanie; Michaelis, Martin; Kleinschmidt-Dörr, Kerstin (Frontiers in Physiology, 2023)
Objective: Osteoarthritis (OA) is a common joint disorder often affecting the knee. It is characterized by alterations of various joint tissues including subchondral bone and by chronic pain. Anti-nerve growth factor (NGF) antibodies have demonstrated improvement in pain associated with OA in phase 3 clinical trials but have not been approved due to an increased risk of developing rapidly progressive OA. The aim of this study was to investigate effects of systemic anti-NGF-treatment on structure and symptoms in rabbits with surgically induced joint instability.Methods: This was elicited by anterior cruciate ligament transection and partial resection of the medial meniscus in right knee of 63 female rabbits, housed altogether in a 56m² floor husbandry. Rabbits received either 0.1, 1 or 3 mg/kg anti-NGF antibody intra-venously at weeks 1, 5 and 14 after surgery or vehicle. During in-life phase, static incapacitance tests were performed and joint diameter was measured. Following necropsy, gross morphological scoring and micro-computed tomography analysis of subchondral bone and cartilage were performed.Results: After surgery, rabbits unloaded operated joints, which was improved with 0.3 and 3 mg/kg anti-NGF compared to vehicle injection during the first half of the study. The diameter of operated knee joints increased over contralateral measures. This increase was bigger in anti-NGF treated rabbits beginning two weeks after the first IV injection and became dose-dependent and more pronounced with time.In the 3 mg/kg anti-NGF group, the bone volume fraction and trabecular thickness increased in the medio-femoral region of operated joints compared to contralateral and to vehicle-treated animals, while cartilage volume and to a lesser extent thickness decreased. Enlarged bony areas were found in right medio-femoral cartilage surfaces of animals receiving 1 and 3 mg/kg anti-NGF. Alterations of all structural parameters were particularly distinct in a subgroup of three rabbits, which also exhibited more prominent symptomatic improvement.This study showed that anti-NGF administration exerted negative impact on structure in destabilized joints of rabbits, while pain-induced unloading of joints was improved. Our findings open up the possibility to better understand the effects of systemic anti-NGF, particularly on subchondral bone, and thus the occurrence of rapidly progressive OA in patients.